2018
DOI: 10.1161/jaha.118.008926
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Aging‐Induced Increases in Aortic Stiffness by Targeting Cytoskeletal Protein‐Protein Interfaces

Abstract: BackgroundThe proximal aorta normally functions as a critical shock absorber that protects small downstream vessels from damage by pressure and flow pulsatility generated by the heart during systole. This shock absorber function is impaired with age because of aortic stiffening.Methods and ResultsWe examined the contribution of common genetic variation to aortic stiffness in humans by interrogating results from the AortaGen Consortium genome‐wide association study of carotid‐femoral pulse wave velocity. Common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In both rodents and humans the stiffness of the proximal aorta increases with age, augmenting systolic blood pressure (BP) pulsatility and increasing the risk of CV events [ 21 23 ]. The proximal aorta is hypothesized to be a shock absorber, but with age, high pulses of pressure that can damage the brain microvasculature are sent to the small delicate blood vessels downstream [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both rodents and humans the stiffness of the proximal aorta increases with age, augmenting systolic blood pressure (BP) pulsatility and increasing the risk of CV events [ 21 23 ]. The proximal aorta is hypothesized to be a shock absorber, but with age, high pulses of pressure that can damage the brain microvasculature are sent to the small delicate blood vessels downstream [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, CMBs, also known as microhemorrhages, are biomarkers of aging, hypo-intense on GRE MRI, associated with geriatrics, cognitive impairment, and risk of stroke [17][18][19][20]. As the stiffness of the proximal aorta increases with age, [21][22][23] high pulses of pressure are sent to the small delicate blood vessels downstream. These pulses could damage the cerebral vessel walls in a way that increases leaking of blood into vulnerable brain regions, a possible mechanism for CMBs formation [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Thus stiffening can interfere with flow-mediated dilation, both by the reduction of the hyperemic stimulus and by the production of abnormal flow patterns that adversely affect endothelial function. Conversely, abnormal endothelial function may modulate aortic stiffness by the alteration of the activation state of smooth muscle in the aortic wall (74), resulting in the potential for a vicious cycle of stiffening and endothelial dysfunction. As a result of the foregoing effects, blunted microvascular hyperemia is associated with CVD events and partially mediates the relation between aortic stiffness and CVD events (1,25).…”
Section: Crosstalk Between Aortic Stiffness and Microvascular Structumentioning
confidence: 99%
“…More recently, it has been shown that the vascular smooth muscle cell (VSMC) [14][15][16][17] also undergoes aging-dependent changes that increase its stiffness and, as a result, the stiffness of the aortic wall. Within the VSMC, the activity of the contractile filaments as well as the molecular signaling pathways that regulate actin polymerization and focal adhesion (FA) signaling, are sources of increases in vascular stiffness with age [18]. It has only recently been recognized that regulation of the stiffness of the cytoskeleton of the VSMC can contribute up to 50% of total aortic stiffness even in young adult aortas in mouse models [16].…”
Section: Components Of Vascular Stiffening With Agementioning
confidence: 99%